Supply Chain Integration: Level of Existence in Green Supply Chain Management Practices among Malaysian ISO 14001 Manufacturing Firms - Rohani Abdullah; Marini Nurbanum Mohamad; Ramayah Thurasamy (International Journal of Supply Chain Management, 2017)
This paper examines the level of existence of supply chain integration, which covers supplier integration, internal integration and customer integration. From the literature, the level of supply chain integration among Malaysian manufacturing firms has yet to be identified. This empirical research was conducted in firms that implement green supply chain management practices and are ISO 14001 certified. Results showed that manufacturing firms in Malaysia practiced a highly progressive level of supply chain integration. Between supplier integration, internal integration and customer integration, internal integration was the most adopted. These findings provided an evaluation on the current level of supply chain integration and therefore provided insights to the importance of supply chain integration in firms that implement green supply chain management practices. Keywords- Supply chain integration, Green Supply Chain Management Practices, ISO 14001, manufacturing firm.